The estimation of productivity of some introduced and local varieties of grain crops in the Republic of Dagestan - M. G. Muslimov; K. U. Kurkiev; N. S. Taymazova; N. A. Kovtunova; S. I. Gorpinichenko (Зерновое хозяйство России, 2019)
Despite the favorable conditions for the cultivation of grain crops in the Republic of Dagestan (i. e. high levels of active solar radiation, sufficient heat, presence of an irrigation network, fertile soils), high yields of grain crops cannot be guaranteed every year, because high humidity, high agro background and strong winds contribute to the spread of fungal diseases, tall height resulted in lodging and deterioration of grain quality. Therefore, the research on the rate of plant response to certain growing conditions and selection of the most adaptive and productive lines and varieties, their introduction into breeding programs and introduction into production are of great importance. Updating of the genetic material through the introduction of new initial forms is one of the ways of successful breeding of the grain crops. In 2015–2017 in the southern lowland of the Republic of Dagestan there was carried out the scientific study of the productivity and resistance to the unfavorable factors of new promising lines and varieties of wheat, triticale and sorghum of different genetic composition and ecological-geographical origin. The research material was the variety samples and lines of wheat, triticale and sorghum, taken both from the world collection of the FSBSI “FITs VIGRR named after N. I. Vavilov”, FSBSI “Agricultural Scientific Center “Donskoy” and Dagestan selection, identified by a complex of breeding significant traits. The highest degree of adaptability in the conditions of Dagestan as demonstrated by the winter soft wheat variety “Fortuna” and the triticale variety “Kaskad”, with the maximum yield of 6.30 and 6.83 t/ha respectively. Among the studied sorghum varieties there should be distinguished the variety “Zernogradskoe 88”, which is characterized with the highest grain yield (4.35 t/ha) and a low height (98 cm) and it ripens before the others because of high adaptability to the growing conditions. The selected varieties of grain crops are of great interest both for breeding work and for direct introduction into the agricultural production of the Republic of Dagestan.